Pelatihan Senam Ibu Hamil terhadap Penurunan Low Back Pain Ibu Hamil Trimester III Di Klinik Bidang Titiek Makassar - Yusrah Taqiyah; Fatma Jama (Yayasan Literasi Sains Indonesia, 2024)
Complaints of pregnant women back pain (back pain) 60-80%. Low Back Pain in pregnancy at 13 weeks to 30 weeks of gestation it was found that the older the pregnancy the stronger the back pain. Gymnastics is a coping method that can prevent physical stress due to pregnancy, reduce lower extremity and back cramps, increase the mother's ability to adapt to changes in her body. The method used in this service activity is in the form of lectures, demonstrations and training. The stages in this activity start from preparation, implementation to closing. Evaluation of the success of the training is assessed through a pre test and post test through a questionnaire. The results obtained on the back pain scale before doing exercise for pregnant women were 3 people with a mild pain scale, 4 people with a moderate pain scale, and 3 other mothers. pregnant, improving blood circulation, reducing complaints of cramps or aches, and preparing breathing, muscle activity and the pelvis to face the birth process. So it is recommended for pregnant women and health workers to apply the exercise method for pregnant women in reducing complaints of back pain during the third trimester.